2011
DOI: 10.1007/s10236-011-0412-9
|View full text |Cite
|
Sign up to set email alerts
|

Tidal and wind-driven surface currents in the German Bight: HFR observations versus model simulations

Abstract: Tidal and wind-driven surface currents in the German Bight between shallow mudflats of the North Frisian islands and the island of Helgoland are studied using coastal high-frequency radar (HFR) observations and hindcasts from a primitive equation numerical model. The setup of the observational system is described, and estimates of expected measurement errors are given. A quantitative comparison of numerical model results and observations is performed. The dominant tidal components are extracted from the two da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 38 publications
9
27
0
Order By: Relevance
“…With their large area coverage, high resolution in time and space, and long-term operational capabilities, the radar systems have enhanced the coastal ocean monitoring capabilities for surface currents (Paduan and Rosenfeld, 1996) and have enabled the development of new data products. The value of HF radar data for the investigation of circulation in the German Bight was demonstrated by Carbajal and Pohlmann (2004) and Port et al (2011). Currently, an observation network of three Wellen radars (WERAs) in the German Bight operates as part of the COSYNA preoperational system (see Fig.…”
Section: The Variables Of Interest For Coastal Applications Includementioning
confidence: 94%
“…With their large area coverage, high resolution in time and space, and long-term operational capabilities, the radar systems have enhanced the coastal ocean monitoring capabilities for surface currents (Paduan and Rosenfeld, 1996) and have enabled the development of new data products. The value of HF radar data for the investigation of circulation in the German Bight was demonstrated by Carbajal and Pohlmann (2004) and Port et al (2011). Currently, an observation network of three Wellen radars (WERAs) in the German Bight operates as part of the COSYNA preoperational system (see Fig.…”
Section: The Variables Of Interest For Coastal Applications Includementioning
confidence: 94%
“…9a and e). For this region, Port et al (2011) identified a higher variability of surface currents, less correlated with wind conditions, which would imply that introducing either Stokes drift or an additional wind drag could probably be a less promising approach for model improvement. However, still the most probable explanation for the mismatch of observations and corresponding simulations is that the drifter experienced problems with its drogue.…”
Section: Discussionmentioning
confidence: 99%
“…The recent progress due to intercomparisons between observations and numerical modelling (Staneva et al, 2009) is currently extended in COSYNA activities towards more profound regional analyses (Port et al, 2011) and data assimilation (SchulzStellenfleth et al, 2011). More details on the characteristic circulation features can be found in the above mentioned papers.…”
Section: Numerical Modelsmentioning
confidence: 99%
“…A number of studies demonstrated that valuable information about small scale hydrodynamic processes can be gathered by statistical analysis of HF radar measurements (e.g., Gough et al, 2010;Prandle, 1987;Port et al, 2011). Another promising application of HF radar data is the assimilation in numerical models in order to improve ocean forecasts.…”
Section: Reconstruction Of Tidal Currents Based On Radial Component Mmentioning
confidence: 99%